Richmond, Mo., Rev. Ordinances no. 31, § 10 (1910) - (:unkn) unknown (My University, 1910)
A law regulating weapons: carrying concealed or in certain places, brandishing, and sales to minors, Ordinance No. 31, § 10: If any person shall carry, concealed upon or about his person any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship, or into any school room where people have assembled for educational, literary or social purposes, or to any election precinct on any election day, or into any court room during the setting of court, or into any other public assemblage of persons met for lawful purpose, other than for military drill or meetings called under the militia law of this state, having upon or about his person, any kind of fire-arms, bowie knife, dirk, dagger, slung shot or other deadly weapon, or shall, in the presence of one or more persons, exhibit such weapon in a rude, angry and threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating drink, or shall directly or indirectly loan or barter to any minor, any such weapon without the consent of the parent or guardian of such minor, he shall upon conviction be punished by a fine of not less than fifty dollars nor more than one hundred dollars, or by imprisonment in the city prison not less than five days nor more than six months, or by both such fine and imprisonment."
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS